4x+10yz-3=0

Simple and best practice solution for 4x+10yz-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+10yz-3=0 equation:


Simplifying
4x + 10yz + -3 = 0

Reorder the terms:
-3 + 4x + 10yz = 0

Solving
-3 + 4x + 10yz = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 4x + 3 + 10yz = 0 + 3

Reorder the terms:
-3 + 3 + 4x + 10yz = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 4x + 10yz = 0 + 3
4x + 10yz = 0 + 3

Combine like terms: 0 + 3 = 3
4x + 10yz = 3

Add '-10yz' to each side of the equation.
4x + 10yz + -10yz = 3 + -10yz

Combine like terms: 10yz + -10yz = 0
4x + 0 = 3 + -10yz
4x = 3 + -10yz

Divide each side by '4'.
x = 0.75 + -2.5yz

Simplifying
x = 0.75 + -2.5yz

See similar equations:

| -5(3x+3)+4=-71 | | 4(1+4k)-3= | | 5((1/2)-3) | | (12x+66)+(2x+20)=9 | | 2(3f+1)= | | -6(1+6x)-1= | | 4n+3(6n-1)=-135 | | 5(1/2-3) | | 2x-17=7x+12 | | 10x+9=7x+8 | | 8p+4=7+7p | | cx+b=5(x-c) | | 4-(3n-3)= | | -14y+28+6x=-44 | | -5*a+(-5*b)=3 | | 32+0.25y=50 | | log(x)=-22.7 | | 1/2•32= | | -268=12(x)-4 | | 8b+8(1-8b)= | | -268=4-12(x) | | 5/9x3/15 | | F(3)=1/2•32 | | 2x+-9(2)=9 | | 4-12(x)=-268 | | 2x+-9(0)=9 | | 9(12/7)+7= | | .55=log(x) | | 3x-6x+6=x-5+11 | | -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= |

Equations solver categories